Genetic analysis and cAMP measurement: comparison between lean and obese anovulating mice - Daniela Berguio Vidotti; Beatriz Schnabel; Mariane Secco; Priscila Cardoso Cristovam; Ricardo Carneiro Borra; Ismael Dale Cotrim Guerreiro da Silva (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2015)
PURPOSE: To evaluate genes differentially expressed in ovaries from lean (wild type) and obese (ob/ob) female mice and cyclic AMP production in both groups.METHODS: The expression on messenger RNA levels of 84 genes concerning obesity was analyzed through the PCR array, and cyclic AMP was quantified by the enzyme immunoassay method.RESULTS: The most downregulated genes in the Obesity Group included adenylate cyclase-activating polypeptide type 1, somatostatin, apolipoprotein A4, pancreatic colipase, and interleukin-1 beta. The mean decrease in expression levels of these genes was around 96, 40, 9, 4.2 and 3.6-fold, respectively. On the other hand, the most upregulated genes in the Obesity Group were receptor (calcitonin) activity-modifying protein 3, peroxisome proliferator activated receptor alpha, calcitonin receptor, and corticotropin-releasing hormone receptor 1. The increase means in the expression levels of such genes were 2.3, 2.7, 4.8 and 6.3-fold, respectively. The ovarian cyclic AMP production was significantly higher in ob/ob female mice (2,229±52 fMol) compared to the Control Group (1,814±45 fMol).CONCLUSIONS: Obese and anovulatory female mice have reduced reproductive hormone levels and altered ovogenesis. Several genes have their expression levels altered when leptin is absent, especially adenylate cyclase-activating polypeptide type 1.